2008
DOI: 10.1378/chest.07-1709
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cardiopulmonary Failure in a Young Man

Abstract: A previously healthy 24-year-old man presented with a 2-day history of fever, myalgias, nausea, and vomiting. On the morning of hospital admission, cough and progressive dyspnea developed in the patient. He denied other symptoms, including chest pain, abdominal pain, or sore throat. This military recruit had been participating in field training in southern New Mexico for 2 weeks prior to presentation and had previously been living in Maricopa County, AZ. He lived in field barracks but denied sick contacts, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Person-to-person transmission has been reported in a few cases, generally associated with a specific strain, the Andes virus (8) . In Brazil, 610 cases of HPS were reported from 1993 to November 2005, most occurring in the southern and southeastern regions of the country (15) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Person-to-person transmission has been reported in a few cases, generally associated with a specific strain, the Andes virus (8) . In Brazil, 610 cases of HPS were reported from 1993 to November 2005, most occurring in the southern and southeastern regions of the country (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Hantavirus can affect humans after inhalation of aerosolized virus particles from urine, saliva, or dried excreta of reservoir rodents ( 11 , 14 ) . Person-to-person transmission has been reported in a few cases, generally associated with a specific strain, the Andes virus ( 8 ) . In Brazil, 610 cases of HPS were reported from 1993 to November 2005, most occurring in the southern and southeastern regions of the country ( 15 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the high incidence and lethality of hantavirus pulmonary syndrome (HPS), there is limited information in the literature about the high-resolution computed tomography (HRCT) features of the disease. There have been only a few case reports describing the tomographic findings of HPS ( 1 - 3 ) , and there have been none presenting HRCT findings in a series of patients. In the previous issue of Radiologia Brasileira , Barbosa et al ( 4 ) published an important study on the HRCT findings in eight patients with confirmed HPS.…”
mentioning
confidence: 99%